Indonesia 5G Channel Model Under Foliage Effect - Khoirul Anwar; Evander Christy; Rina Pudji Astuti (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2019)
Abstract The performance of communications is determined by the channel, therefore knowledge of channel model of a country is important. This paper proposes (i) the fifth telecommunication generation (5G) Indonesia channel model and (ii) a framework to derive the channel model of any locations in Indonesia. We consider operating frequency of 3.3 GHz with bandwidth of 40 MHz with real-field parameters of several cities in Indonesia. We also present a theoretical outage performance evaluated for the proposed Indonesia 5G channel model validated by block error rate (BLER) performances of cyclic-prefix orthogonal frequency division multiplexing (CP-OFDM) numerology zero with 5G complex binary phase shift keying (C-BPSK) and Polar coding scheme. Sub-optimal Polar codes are used in this research, where better performances are expected in the future. We found that the Indonesia 5G channel model has 17 paths for the case of without foliage effect and has less than 15 paths for the case of with foliage effect. The results show that foliage attenuation causes performance degradations indicated by smaller number of paths and worse theoretical outage performances. The obtained outage performances from the proposed Indonesia 5G channel model in this paper are expected to be a reference for 5G implementations in Indonesia. Abstrak Kinerja sistem komunikasi ditentukan oleh kanal, sehingga pengetahuan model kanal suatu negara menjadi penting. Makalah ini mengusulkan (i) model kanal telekomunikasi generasi ke-lima (5G) Indonesia dan (ii) kerangka kerja untuk menghitung model kanal di lokasi lain di Indonesia. Model kanal dalam makalah ini diciptakan untuk bandwidth 40 MHz pada frekuensi 3,3 GHz dengan parameter riil lapangan. Makalah ini juga menampilkan teori outage performance yang diperoleh dari model kanal 5G Indonesia, kemudian memvalidasi teori outage performance tersebut menggunakan block error rate (BLER) pada cyclic-prefix orthogonal frequency division multiplexing (CP-OFDM) numerology zero dengan complex binary phase shift keying (C-BPSK) standard 5G dan Polar coding. Semua hasil numerik diperoleh dari simulasi komputer menggunakan parameter riil lapangan untuk alam Indonesia. Makalah ini menemukan bahwa kanal 5G Indonesia dapat dimodelkan power delay profile (PDP) dengan 17 path untuk kanal tanpa efek dedaunan dan kurang dari 15 path untuk kanal dengan dedaunan. Hasil tersebut menunjukkan bahwa redaman daun menyebabkan penurunan kinerja, yang ditandai dengan penurunan jumlah path dan memburuknya outage performance. Kurva outage performance yang diperoleh dari model kanal 5G Indonesia diharapkan menjadi referensi untuk implementasi sistem 5G di Indonesia dalam pengembangan 5G di Indonesia secara optimal, terutama untuk lokasi yang memiliki dedaunan lebat.